GE_GERICHTE P/11373/2013 vom 23. Februar 2015 - GE Cour de justice (2015)
PRÉSOMPTION D'INNOCENCE; IN DUBIO PRO REO; PEINE PÉCUNIAIRE; EXHIBITIONNISME; EXEMPTION DE PEINE | CEDH.6.2; Cst.32.1; CPP.10.3; CP.194.1; CP.34.1; CP.34.2; CP.52; CP.194.2